The importance of financial failure models as a mechanism for judging the extent of the companies ability to continue by Using of ALTMAN and KIDA models - Case study of Saudi Qassim Cement Company - - kherifi, houssam; Mahieddine, Mahmoud Omar (Journal of Research in Finance and Accounting, 2026)
This study aims to investigate the extent to which the contribution of models for predicting financial failure in judging the continuity of the economic companies activity by using the ALTMAN and KIDA models. To achieve the purpose of study، the ALTMAN and KIDA models was applied on the Saudi “Qassim” Cement Company، depending on the financial statement for (05) sequent years from 2016 to 2020. The study concluded to several results، the important one is possibility of depending on results of the ALTMAN and KIDA models in order to predict financial failure and prevent its occurrence or reduce its risk by taking appropriate corrective measures in right time and manner to ensure the continuity of the company and this is what was reach for it، with regard to Al-Qassim company، which was revealed after analysis and explanation. The results of the two models stated that it faced several problems، especially in 2017 and 2018 due to poor profitability and lack of liquidity compared to the size of its investments in assets، this led the company to treatment the problem and work to avoid its falling into financial failure.